Spotlight on USP30: structure, function, disease and target inhibition - Du, Jiapeng; Gao, Yiyang; Xue, Guoqing; Zhao, Zhuoyue; Yang, Ying; Chu, Peng; Duan, Xingping (Frontiers in Pharmacology, 2025)
This review comprehensively summarizes the current understanding of ubiquitin-specific protease 30 (USP30), covering its structural characteristics, functions in cellular processes, associations with diseases, diagnostic and therapeutic strategies, as well as controversies and future perspectives. USP30, a deubiquitinating enzyme, plays crucial roles in mitochondrial quality control, autophagy regulation, and cellular homeostasis. It is implicated in the progression of several malignancies, including hepatocellular carcinoma, breast carcinoma, and glioblastoma, as well as neurodegenerative disorders such as Parkinson’s disease. This involvement is mediated through its regulation of mitochondrial autophagy, stabilization of oncoproteins like Snail and c-Myc, and facilitation of metabolic reprogramming. Inhibition of USP30 has demonstrated potential in reversing the malignant phenotype of tumors and enhancing neuroprotection, highlighting its promise as a versatile therapeutic target. Pharmacological inhibition of USP30, using agents such as S3, MF-094, and FT3967385, enhances ubiquitination and reactivates mitophagy, indicating potential therapeutic benefits in preclinical models. The development of USP30-targeted therapies holds promise but also faces challenges. Further research on USP30 is expected to provide new insights into disease mechanisms and therapeutic interventions.